2019
DOI: 10.1111/gbb.12630
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the developmental trajectory of mouse models of neurodevelopmental disorders: Social and communication deficits in mice with Neurexin 1α deletion

Abstract: Neurexin 1α mutations are strongly associated with neurodevelopmental disorders such as autism spectrum disorders and schizophrenia in humans. Studies using the Neurexin 1α knock‐out mouse have showed behavioral abnormalities of relevance to these disorders and baseline deficits in excitatory synaptic function have been described. However, little is known about the effect of Neurexin 1α deletion on behavior during development. This study examined the effects of Neurexin 1α deletion on behavior across a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 73 publications
3
31
0
Order By: Relevance
“…Mice lacking Nrxn1 exhibit deficits in core symptoms related to ASD. Specifically, Nrxn1α mutants display deficits in the social domain including increased social preference, decreased social investigation, decreased social interaction, and increased aggression [ 35 , 46 , 47 , 48 ]. Furthermore, they show stereotypic and repetitive behaviors such as increased grooming, impaired nest-building, altered novelty responsiveness, and habituation [ 31 , 35 , 38 ].…”
Section: From Human Asd Genetics To Translational Behavioral Phenotype In Mouse Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice lacking Nrxn1 exhibit deficits in core symptoms related to ASD. Specifically, Nrxn1α mutants display deficits in the social domain including increased social preference, decreased social investigation, decreased social interaction, and increased aggression [ 35 , 46 , 47 , 48 ]. Furthermore, they show stereotypic and repetitive behaviors such as increased grooming, impaired nest-building, altered novelty responsiveness, and habituation [ 31 , 35 , 38 ].…”
Section: From Human Asd Genetics To Translational Behavioral Phenotype In Mouse Modelsmentioning
confidence: 99%
“…Furthermore, they show stereotypic and repetitive behaviors such as increased grooming, impaired nest-building, altered novelty responsiveness, and habituation [ 31 , 35 , 38 ]. In addition, several behaviors were reported that relate to ASD comorbidities including deficits in learning and cognition, locomotor activity, motor performance, award processing, and anxiety-like behaviors [ 31 , 35 , 36 , 38 , 46 , 47 , 48 , 49 ]. Although the social, stereotyped, and repetitive behaviors are commonly studied, sensory behaviors have received less attention in this model.…”
Section: From Human Asd Genetics To Translational Behavioral Phenotype In Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes may be associated with the higher muscle polyunsaturated fatty acid content in this new carp strain ( Shengyan et al, 2018 ). The last class is associated with nerve regulation; e.g., neurexin-1a is strongly associated with neurodevelopmental disorders, so knockout mice exhibited social deficits and increased levels of aggression ( Armstrong et al, 2020 ); Krueppel-like factor 13 inhibits neurite/axon growth in hippocampal neurons partially by inhibiting the cAMP signaling pathway ( Ávila-Mendoza et al, 2020 ). These nerve regulation-related genes may be a reflection of the microbiota-gut-brain axis ( Cryan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed inspection of these functional groups further revealed enrichment of genes that are essential in nervous system development (Figure 4a,b). Several key promoters and regulators in central nervous system development (Nitric Oxide Synthase 1 (NOS1) [33][34][35][36]), neuron differentiation (T-box Transcription Factor 3 (TBX3) [37], Desmoplakin 3 (DPF3) [38,39], Bone Morphogenetic Protein 4 (BMP4) [37,40]) and neuronal development (Neurexin 2 (NRXN2) [41,42], Ataxin 1 (ATXN1) [43,44]) were upregulated, supporting neuronal differentiation [45] (Figure 4a,b). Additionally, there was also a prevalence of functional groups associated with cell division regulation including the mitotic cell cycle, nuclear division, regulation of metaphase/anaphase transition of the cell cycle, regulation of chromosome separation and spindle organization (Figure 3c,d).…”
Section: Gene Expression Profiles Characteristic Of Growth Arrest and Nervous System Development Are Induced By Sustained Low-dose Panobimentioning
confidence: 97%